Peran Perbankan Syariah dalam Mengembangkan UMKM di Masa Pandemi Covid-19 - Rafiuddin, Muhammad; Hasan, Asyari (Jurnal Samudra Ekonomi dan Bisnis, 2023)
The study aims to analyze the role of Islamic banking in efforts to develop MSMEs during the Covid-19 pandemic in terms of the financing provided. The method used is quantitative descriptive by presenting information about the development of Islamic banking financing from 2017-2020. Assets owned by Islamic banking continue to increase from year to year, three years in a row before the entry of the Covid-19 pandemic to Indonesia. Islamic banking assets continue to increase even in 2020 where the pandemic has started to enter Indonesia, it can be seen that Islamic banking assets continue to increase to close to Rp. 70 trillion from the previous year. Turnover of funds in various business sectors carried out by Islamic banks is increasing from year to year, but is also always accompanied by an increase in non-performing financing.